Metal formic acid framework material and method of making same

CN122941013APending Publication Date: 2026-10-20NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611190919.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

以甲酸镁框架材料的合成为例,现有方法通常需要使用过量甲酸作为溶剂,或者采用N,N-二甲基甲酰胺(DMF)作为溶剂进行溶剂热反应,而甲酸和DMF受热情况下会发生自分解,甲酸会分解为水和一氧化碳,DMF会分解为二甲胺,在溶剂额外损失的同时还会导致溶剂纯度降低,此外由于甲酸和DMF均为强极性溶剂,非常容易吸水导致溶剂纯度降低,因此它们的回收利用很复杂,而且甲酸作为强腐蚀性溶剂,对管路钢材质量要求极高

Benefits of technology

本申请通过将水合金属甲酸盐直接转晶的方式,克服了传统溶剂热方法的溶剂选择局限性,本申请使用典型的极性分子即可实现水合金属甲酸盐向金属甲酸多孔材料的转化,因此原料供应情况受市场波动影响大幅降低;同时,真空环境下也可实现水合金属甲酸盐转晶,完全避免了合成过程中溶剂的使用,进而避免了合成后溶剂回收再利用的难题;本申请通过水合金属甲酸盐转晶制备金属甲酸框架材料,能够大幅降低多孔结构结晶所需的时间,将多孔框架材料的合成时间从传统文献的48小时降低至6小时甚至更低;并且本申请能够将几乎全部原料完全转化为多孔框架材料,具有接近100%的产率,相比传统溶剂热合成方案的70%左右的产率,有了极大的提升,对金属甲酸框架材料的工业化生产具有重大意义。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to the field of porous framework materials technology, and provides a metal formate framework material and its preparation method. The metal formate framework material described in this application is obtained by the preparation method described in this application; the preparation method includes: heating under vacuum and / or in the presence of polar molecules to directly transform the crystal structure of hydrated metal formate into a porous framework topology, thereby obtaining the metal formate framework material. By transforming the hydrated metal formate crystal under specific conditions, the formic acid ligands are rearranged to obtain the metal formate framework material. This overcomes the limitations of traditional metal formate framework material preparation that relies on excess formic acid or N,N-dimethylformamide solvent, avoids many negative impacts caused by the thermal decomposition of formic acid and N,N-dimethylformamide, significantly shortens the synthesis temperature and cycle, and overcomes the problems of partial solvent decomposition and difficulty in recycling during the synthesis of metal formate framework materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of porous framework material preparation technology, and particularly relates to a metal formic acid framework material and its preparation method. Background Technology

[0002] Porous materials, due to their large specific surface area, abundant pore structure, and tunable surface chemistry, have broad application prospects in catalysis, adsorption separation, energy storage, sensing, and environmental remediation. Among porous materials, metal-organic frameworks (MOFs), structures composed of metals and organic ligands, have become a focus of attention in academia and industry in recent years. MOFs possess well-defined structural compositions and highly tunable physicochemical properties, thus attracting considerable research interest. Developing simple, low-cost, and controllable methods to prepare structurally stable, highly porous materials is a key focus in the field of coordination polymers.

[0003] Metal formates, as a class of metal-organic framework materials with relatively simple structures, possess advantages such as inexpensive and readily available raw materials, mild synthesis conditions, and well-defined coordination structures, demonstrating promising application potential in areas such as carbon dioxide adsorption and separation, trifluoropropane / trifluoropropylene separation, and ethylene / propylene separation. Especially for porous metal formate materials, the low cost of their precursor raw materials is one of their significant advantages compared to other porous materials. However, the synthesis cost depends not only on the price of raw materials but also on solvent consumption and solvent recovery and regeneration during the synthesis process; the latter often has a more significant impact on the cost of large-scale production. Existing synthetic methods for metal formate framework materials typically rely on organic solvents or excess formic acid as the reaction medium. Taking the synthesis of magnesium formate framework materials as an example, existing methods usually require the use of excess formic acid as a solvent, or the use of N,N-dimethylformamide (DMF) as a solvent for a solvothermal reaction. Formic acid and DMF will undergo self-decomposition when heated. Formic acid will decompose into water and carbon monoxide, and DMF will decompose into dimethylamine. In addition to the extra loss of solvent, the purity of the solvent will also decrease. Furthermore, since formic acid and DMF are both highly polar solvents, they are very easy to absorb water, which will reduce the purity of the solvent. Therefore, their recycling is very complicated. Moreover, as a highly corrosive solvent, formic acid has extremely high requirements for the quality of the pipe steel.

[0004] In summary, under solvothermal conditions, both formic acid and DMF inevitably undergo some degree of decomposition, resulting in significant solvent loss, which is detrimental to reducing production costs and achieving green preparation. Furthermore, metal salt precursors typically have poor solubility in organic solvents, making uniform dissolution difficult, thus limiting the range of solvent options and adversely affecting the product formation process and synthetic stability.

[0005] Therefore, how to develop a method for preparing metal formic acid framework materials with low solvent consumption, good raw material adaptability, and suitability for large-scale preparation remains a technical problem that urgently needs to be solved in this field.

[0006] In view of this, the present invention is hereby proposed. Summary of the Invention

[0007] The purpose of this application is to provide a metal formic acid framework material and a method for preparing the same, in order to solve the above-mentioned problems.

[0008] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a method for preparing a metal formate framework material, the method comprising: performing heat treatment under vacuum atmosphere and / or in the presence of polar molecules to directly transform the crystal structure of hydrated metal formate into a porous framework topology, thereby obtaining a metal formate framework material.

[0009] The vacuum atmosphere is a negative pressure environment; preferably, when the standard atmospheric pressure is 101.3 kPa, the pressure of the vacuum atmosphere is 0~101 kPa; optionally, when the standard atmospheric pressure is 101.3 kPa, the pressure of the vacuum atmosphere can be any value among 0, 10 kPa, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80 kPa, 90 kPa, 100 kPa and 101 kPa. More preferably, the pressure of the vacuum atmosphere is 50 kPa; And / or, The conditions for the existence of the polar molecules include any one or more of the following: directly using polar molecules as a solvent, using an inert gas to carry polar molecules, and the self-evaporation of polar molecules.

[0010] Preferably, the polar molecule includes one or more of the following: water, ketones, esters, ethers, acids, alcohols, nitriles, sulfur compounds, amines, aldehydes, and carbonates.

[0011] More preferably, the polar molecule is an acetonitrile molecule.

[0012] Alternatively, this application can directly use acetonitrile as a solvent to dissolve the hydrated metal formate in acetonitrile solvent, and then perform the specific heat treatment of this application to obtain the metal formate framework material.

[0013] Preferably, the hydrated metal formate includes one or more of zinc formate, manganese formate, cobalt formate, magnesium formate, vanadium formate, zirconium formate, calcium formate, molybdenum formate, iron formate, nickel formate, copper formate, tin formate, niobium formate, scandium formate, and rare earth formate.

[0014] Preferably, the heat treatment includes any one of: direct heating, closed container heating, heating under inert gas protection, microwave heating, and mechanical ball milling; And / or, The target temperature for the heat treatment is 50~250℃, and the time is 0.1~100h.

[0015] Optionally, the target temperature for the heat treatment can be any value between 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 150℃, 180℃, 200℃, 220℃, 240℃, and 250℃, and the time can be any value between 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, 75h, 80h, 85h, 90h, 95h, and 100h. More preferably, the target temperature for the heat treatment is 100°C, and the time is 6 hours.

[0016] The hydrated metal formate described in this application refers to a one-dimensional chain structure formed by the deprotonation of formic acid to become a formate anion, with oxygen atoms coordinating with metal ions. Each metal ion on the one-dimensional chain is coordinated by four formic acids at the oxygen end. At the same time, due to the unsaturated coordination of the metal, the two vacant coordination sites are used by two water molecules, which form coordinated water. Hydrated metal formate usually does not have a porous structure and its crystallinity is usually poor after heating.

[0017] The hydrated metal formate used in this application can be a commercially available, mature product; it can also be prepared by the following method: in an aqueous solution, the coordination process between the metal salt precursor and the formic acid ligand is first completed, followed by evaporation and crystallization to obtain the hydrated metal formate. The metal in the metal salt precursor is selected from transition metals or alkaline earth metals; preferably, the metal in the metal salt precursor includes one or more of zinc, manganese, cobalt, magnesium, vanadium, zirconium, calcium, molybdenum, iron, nickel, copper, tin, niobium, titanium, scandium, or rare earth elements.

[0018] This application uses hydrated metal formate as raw material and heats it in a vacuum environment or in the presence of a polar solvent to convert the hydrated metal formate into a porous structure in situ. The method involves removing coordination water and crystal water in a vacuum environment or with a polar solvent, completing the dissociation of water ligands on the metal, and then rearranging the formic acid groups under a heated environment to complete the transformation of the hydrated formate into a porous framework structure.

[0019] Due to the strong coordination ability of electronegative oxygen, water participates in coordination with hydrated metal formates to form coordinated water. At this time, the binding force of water molecules is very strong and cannot be removed by heating alone. This application relies on the outward driving force provided by polar molecules or vacuum environment to pull water molecules out of the metal. Due to the sudden departure of water molecules, the crystal structure forms an amorphous state. At this time, two coordination sites are left on the metal. Heating causes the formic acid ligands in the structure to rearrange, so that the formic acid gradually increases from monodentate coordination to bidentate coordination. The spatial arrangement creates a porous structure, thus ultimately forming a porous framework material.

[0020] Secondly, this application provides a metal formic acid framework material, which is prepared by the method for preparing metal formic acid framework material described in this application.

[0021] The metal formic acid framework material described in this application refers to a porous framework material in which formate anions coordinate with metal ions via oxygen atoms, grow along a specific crystal plane to form a perfect crystal, have a well-defined pore structure and pore volume, can accommodate a large number of guest molecules, and can perform adsorption and separation tasks.

[0022] The metal formate framework material of this application is preferably an alpha-type metal formate framework material.

[0023] Compared with the prior art, this application has the following beneficial effects: This application overcomes the limitations of traditional solvothermal methods by directly converting hydrated metal formate into porous metal formic acid materials. It utilizes typical polar molecules to achieve this conversion, significantly reducing the impact of market fluctuations on raw material supply. Furthermore, the conversion can be performed under vacuum, completely eliminating the need for solvents during synthesis and avoiding the challenges of solvent recovery and reuse. This method significantly reduces the time required for porous structure crystallization, lowering the synthesis time from 48 hours in traditional literature to 6 hours or even less. Moreover, it achieves near-100% yield, converting almost all raw materials into porous framework materials, a substantial improvement over the approximately 70% yield of traditional solvothermal synthesis methods. This has significant implications for the industrial production of metal formic acid framework materials.

[0024] The metal formic acid framework material prepared by the method of this application has high purity, perfect crystallization, and a very high specific surface area, making it suitable for adsorption separation and gas storage technologies. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 The PXRD spectrum of the magnesium alpha formate framework material provided in Example 1; Figure 2 The nitrogen adsorption isotherm of the magnesium alpha formate framework material provided in Example 1; Figure 3 A pore size distribution diagram of the magnesium alpha formate framework material provided in Example 1; Figure 4 The adsorption isotherm of the hexane isomer of the magnesium formate framework material provided in Example 1; Figure 5 The PXRD spectrum of the magnesium alpha formate framework material provided in Example 2; Figure 6 The nitrogen adsorption isotherm of the magnesium alpha formate framework material provided in Example 2; Figure 7 The PXRD spectrum of the magnesium alpha formate framework material provided in Example 3; Figure 8 The PXRD spectrum of the magnesium alpha formate framework material provided in Example 4; Figure 9 The PXRD spectrum of the magnesium alpha formate framework material provided in Example 5; Figure 10 PXRD spectrum of the framework material provided for Comparative Example 1; Figure 11 Adsorption isotherms of the hexane isomer of the framework material provided for Comparative Example 1; Figure 12 The PXRD spectrum of the material provided for Comparative Example 2. Detailed Implementation

[0027] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0028] The following description is based on specific embodiments. It should be noted that the magnesium formate dihydrate used in this application can be a commercially available product, such as the product with CAS number 6150-82-9, brand name Aladdin, and catalog number M343898-10g, or a self-made product that meets the requirements for structure and purity.

[0029] Example 1 According to the method for preparing metal formic acid framework materials provided in this application, a magnesium alpha formic acid framework material is prepared, and the specific steps are as follows: 3g of commercially available magnesium formate dihydrate was placed in the lining of a 50ml hydrothermal reactor, and 50ml of acetonitrile was added. The reactor was then heated at 150℃ for 6 hours in a forced-air drying oven. After the reaction was complete, the product was washed with anhydrous ethanol by centrifugation and then dried to obtain 2.28g of magnesium formate alpha framework material. The atom utilization rate was 100% based on the molar amount of Mg. The PXRD spectrum of the prepared magnesium formate alpha framework material is shown below. Figure 1 As shown.

[0030] The adsorption performance of the magnesium alpha formate framework material prepared in this embodiment was tested, as follows: 1. Nitrogen adsorption performance test Test method: The magnesium alpha formate framework material prepared in this embodiment was activated at 180°C under vacuum for 6 hours, and then its nitrogen adsorption isotherm was measured at 77K using a Bel MAX adsorption instrument.

[0031] Test results: such as Figure 2 As shown, by Figure 2 It can be seen that the nitrogen adsorption isotherm is a type I adsorption.

[0032] The BET specific surface area of ​​the magnesium alpha-formate framework material prepared in this embodiment was calculated to be 529 m² according to the BET equation. 2 g -1 The aperture distribution is as follows Figure 3 As shown.

[0033] 2. Hexane isomer adsorption and separation performance test Test method: The magnesium alpha formate framework material prepared in this embodiment was activated at 180°C under vacuum for 6 hours, and then its adsorption isotherm for hexane isomers was measured at 30°C using a Bestar vapor adsorption instrument.

[0034] Test results: such as Figure 4 As shown; by Figure 4 It can be seen that the magnesium alpha formate framework material prepared in this embodiment exhibits excellent adsorption capacity for n-hexane and good adsorption selectivity for hexane isomers.

[0035] Example 2 According to the method for preparing metal formic acid framework materials provided in this application, a magnesium alpha formic acid framework material is prepared, and the specific steps are as follows: 3g of commercially available magnesium formate dihydrate was placed in a quartz boat. A vacuum was applied to the system to maintain an absolute pressure of 50kPa within the boat. The boat was then placed in a tube furnace and heated at 150℃ for 12 hours. After the reaction was complete, the product, without washing or drying, yielded the magnesium formate framework material. Its PXRD spectrum is shown below. Figure 5 As shown.

[0036] The nitrogen adsorption performance of the magnesium alpha formate framework material prepared in this embodiment was tested, as follows: Test method: The magnesium alpha formate framework material prepared in this embodiment was activated at 180°C under vacuum for 6 hours, and then its nitrogen adsorption isotherm was measured at 77K using a Bel MAX adsorption instrument.

[0037] Test results: such as Figure 6 As shown, by Figure 6 It can be seen that the nitrogen adsorption isotherm is a type I adsorption.

[0038] The BET specific surface area of ​​the magnesium alpha-formate framework material prepared in this embodiment, calculated according to the BET equation, is 532 m². 2 g -1 .

[0039] Example 3 According to the method for preparing metal formic acid framework materials provided in this application, a magnesium alpha formic acid framework material is prepared, and the specific steps are as follows: 3g of commercially available magnesium formate dihydrate was placed in a quartz boat. Using inert carrier gas nitrogen, acetonitrile, a polar solvent, was bubbled through the quartz boat to ensure the magnesium formate dihydrate was in a polar molecular atmosphere. Simultaneously, the quartz boat was placed in a tube furnace and heated at 150°C for 12 hours. After the reaction was complete, the product, without washing or drying, yielded the magnesium formate framework material. Its PXRD spectrum is shown below. Figure 7 As shown.

[0040] Example 4 According to the method for preparing metal formic acid framework materials provided in this application, a magnesium alpha formic acid framework material is prepared, and the specific steps are as follows: 3g of commercially available magnesium formate dihydrate was placed in the lining of a 50ml hydrothermal reactor, and 50ml of formic acid was added. The reactor was then placed in a forced-air drying oven and heated at 80℃ for 6 hours. After the reaction was completed, the product was washed with anhydrous ethanol by centrifugation and then dried to obtain the magnesium formate framework material. Its PXRD spectrum is shown below. Figure 8 As shown.

[0041] Example 5 According to the method for preparing metal formic acid framework materials provided in this application, a magnesium alpha formic acid framework material is prepared, and the specific steps are as follows: 3g of commercially available magnesium formate dihydrate was placed in the lining of a 50ml hydrothermal reactor, and 50ml of acetone was added. The reactor was then placed in a forced-air drying oven and heated at 180℃ for 6 hours. After the reaction was completed, the product was washed with anhydrous ethanol by centrifugation and then dried to obtain the magnesium formate framework material. Its PXRD spectrum is shown below. Figure 9 As shown.

[0042] Comparative Example 1 The magnesium alpha formate framework material was prepared using a traditional classical solvothermal method, and the specific steps are as follows: 5g of magnesium chloride hexahydrate was placed in the lining of a 50ml hydrothermal reactor, 3ml of anhydrous formic acid was added, followed by 20ml of DMF as a solvent. The mixture was stirred until homogeneous, and the reactor was placed in a forced-air drying oven and heated at 120℃ for 48 hours. After the reaction was completed, the product was washed with anhydrous ethanol by centrifugation and then dried to obtain the magnesium alpha formate framework material. Its PXRD spectrum is shown below. Figure 10 As shown.

[0043] The adsorption performance of the magnesium alpha formate framework material prepared in this comparative example for hexane isomers was tested, and the details are as follows: Test method: The magnesium alpha formate framework material prepared in this comparative example was activated at 180℃ under vacuum for 6h, and then its adsorption isotherm for hexane isomers was measured at 30℃ using a Bestar vapor adsorption instrument.

[0044] Test results: such as Figure 11 As shown.

[0045] By comparison Figure 4 The adsorption isotherm of the hexane isomer of the magnesium alpha formate framework material provided in Example 1 and Figure 11The adsorption isotherm of the hexane isomer of the framework material provided in Comparative Example 1 shows that the magnesium alpha formate framework material prepared in this application has higher adsorption selectivity and the adsorption amount of the larger molecular isomers methylpentane and dimethylbutane is greatly reduced. This indicates that the method provided in this application can not only significantly reduce the synthesis cost of the framework material, but also greatly improve the adsorption selectivity of the synthesized framework material.

[0046] Comparative Example 2 10 g of magnesium chloride hexahydrate was dissolved in 100 mL of acetonitrile, and 10 mL of formic acid was added to obtain a mixture. The mixture was stirred at room temperature for 3 hours, and then solvothermal at 120 °C for 24 hours. After the reaction was completed, the product was filtered, washed with ethanol, dried, and characterized. Its PXRD spectrum is shown below. Figure 12 As shown; by Figure 12 It can be seen that, compared with the traditional DMF solvothermal preparation method (such as Comparative Example 1), Figure 10 In comparison, the absence of strong characteristic peaks at the low diffraction peak ends indicates that this method has not effectively synthesized magnesium formate framework materials.

[0047] Traditional metal formate framework materials rely on excess formic acid or N,N-dimethylformamide as solvents for synthesis. This process suffers from high costs, low reaction yields, difficulty in activation, and especially the limited availability of solvents, solvent decomposition, and challenges in solvent recovery. This application attempts to avoid the use of N,N-dimethylformamide solvent and expand the range of available solvents, providing a low-cost method for preparing porous materials from metal formates. Compared to traditional solvothermal synthesis methods, the metal formate framework material obtained by direct conversion of hydrated metal formate crystals proposed in this application exhibits significantly superior adsorption and separation performance. This is because the crystal structure obtained by the crystal conversion method in this application is more perfect, and the crystal growth along the pore direction is more advantageous, thus amplifying the contribution of pore sieving to the adsorption and separation selectivity of the porous material.

[0048] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing a metal formic acid framework material, characterized in that, The preparation method includes: heating under vacuum and / or in the presence of polar molecules to directly transform the crystal structure of hydrated metal formate into a porous framework topology, thereby obtaining a metal formate framework material.

2. The preparation method according to claim 1, characterized in that, The conditions for the existence of the polar molecules include any one or more of the following: directly using polar molecules as a solvent, using an inert gas to carry polar molecules, and the self-evaporation of polar molecules.

3. The preparation method according to claim 1 or 2, characterized in that, The polar molecules include one or more of the following: water, ketones, esters, ethers, acids, alcohols, nitriles, sulfur compounds, amines, aldehydes, and carbonates.

4. The preparation method according to claim 3, characterized in that, The polar molecule is acetonitrile.

5. The preparation method according to claim 1, characterized in that, The hydrated metal formate includes one or more of the following: zinc formate hydrate, manganese formate hydrate, cobalt formate hydrate, magnesium formate hydrate, vanadium formate hydrate, zirconium formate hydrate, calcium formate hydrate, molybdenum formate hydrate, iron formate hydrate, nickel formate hydrate, copper formate hydrate, tin formate hydrate, niobium formate hydrate, scandium formate hydrate, and rare earth formate hydrates.

6. The preparation method according to claim 2, characterized in that, When the standard atmospheric pressure is 101.3 kPa, the pressure of the vacuum atmosphere is 0~101 kPa.

7. The preparation method according to claim 6, characterized in that, The pressure of the vacuum atmosphere is 50 kPa.

8. The preparation method according to claim 1, characterized in that, The heat treatment includes any one of the following: direct heating, closed container heating, heating under inert gas protection, microwave heating, and mechanical ball milling; And / or, The target temperature for the heat treatment is 50~250℃, and the time is 0.1~100h.

9. The preparation method according to claim 8, characterized in that, The target temperature for the heat treatment is 100°C, and the time is 6 hours.

10. A metal formic acid framework material, characterized in that, The metal formic acid framework material is prepared by the method for preparing metal formic acid framework material according to any one of claims 1-9.